2011
DOI: 10.3892/ol.2011.523
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whole-body retention of iodine-131 (131I) after postoperative remnant ablation for differentiated thyroid carcinoma – thyroxine withdrawal versus rhTSH administration: A retrospective comparison

Abstract: Abstract. Previous studies demonstrated that preparation with recombinant human thyroid-stimulating hormone (rhTSH) for thyroid remnant ablation results in lower extrathyroidal radiation compared to hypothyroidism. The results of 50 radioiodine therapies (RITs) under rhTSH, regarding iodine half-life, were evaluated and compared with 50 RITs performed on patients with hypothyroidism following thyroxine withdrawal. The patients were treated with 3700 MBq (100 mCi) of 131 I. Forty-eight hours after RIT, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The mean TSH level of the negative intrathoracic uptake group patients who used rh-TSH (171.5±14.1) was significantly different from that of the negative thoracic uptake group who underwent hormone withdrawal (67.7±14.6) (p =0.001), suggesting that this was due to the use of rh-TSH. It has been reported that the use of rh-TSH produces higher TSH levels compared to thyroid hormone withdrawal [26]. Actually, the TSH level of the indeterminate uptake group of hormone withdrawal patients was higher (76.9±9.8) than that of the negative intrathoracic uptake group of hormone withdrawal patients (67.7±14.6); this was not statistically significant (p =0.081).…”
Section: Discussionmentioning
confidence: 83%
“…The mean TSH level of the negative intrathoracic uptake group patients who used rh-TSH (171.5±14.1) was significantly different from that of the negative thoracic uptake group who underwent hormone withdrawal (67.7±14.6) (p =0.001), suggesting that this was due to the use of rh-TSH. It has been reported that the use of rh-TSH produces higher TSH levels compared to thyroid hormone withdrawal [26]. Actually, the TSH level of the indeterminate uptake group of hormone withdrawal patients was higher (76.9±9.8) than that of the negative intrathoracic uptake group of hormone withdrawal patients (67.7±14.6); this was not statistically significant (p =0.081).…”
Section: Discussionmentioning
confidence: 83%
“…Second, whole-body scintigraphy for response assessment is associated with low radiation exposure and currently in our clinic done almost exclusively with rhTSH. Table 7 compiles publications comparing the effect of hypothyroidism and rhTSH on whole-body dose, half-life, or residence time (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Most publications are based on studies with a limited number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RITh is often given 2-3 wk after surgery (1). Previous studies found differences in radiation exposure between patients treated in hypothyroidism versus rhTSH (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). The aim was to retrospectively examine thyroid uptake and effective half-life in patients with a shorter time interval between surgery and RITh, thus reflecting current therapeutic standards.…”
mentioning
confidence: 99%
“…This type of tumor includes, basically, well‐differentiated papillary thyroid carcinoma (PTC) and follicular thyroid carcinoma (FTC), poorly differentiated carcinoma, and the most dedifferentiated, aggressive thyroid cancer, anaplastic thyroid carcinoma (ATC): all of them arise from one cell type, the thyroid follicular epithelial cell [Saiselet et al, ]. The predominant types of thyroid cancers, however, are PTC, which accounts for more than 80% of all thyroid malignancies, and FTC, for 10% of the well‐differentiated thyroid cancers [Carvalho et al, ].…”
Section: Introductionmentioning
confidence: 99%